Na outra ponta do Brasil: práticas e experiências de inovação no jornalismo científico do Museu Paraense Emílio Goeldi. - MACEDO, Tarcízio Pereira (2020)
This study takes a reflection on innovation in scientific journalism, focusing on three specific categories of practice: 1) business model/management, 2) content and narrative, and 3) technology and format present in scientific journalism of the Museu Paraense Emílio Goeldi (MPEG). Its purpose is to identify and analyze aspects, meanings and modes of innovation in journalism developed in favor of the Public Communication of Science in the Social Communication Service of MPEG. It seeks, therefore, to explore how a secular institution acts in possible innovative tendencies in contemporary journalism in times of convergence. From this perspective, the article specifically investigates the practices and experiences of the Museum's Multimedia Communication Laboratory focused on journalistic innovation in the context of the diffusion and scientific popularization in the Amazon, in order to illustrate each analytical category and to draft a debate on the urgency of the use of aspects of innovation in journalism strategies of scientific institutions in Brazil. The paper also presents a brief critical reading on the Public Communication of Science and the innovation in journalism, whose objective is to provide an update that addresses the importance of this intersection in the study agenda on innovation and for the investment in strategies of innovation in journalism as an alternative for institutions to adapt to the changes imposed by contemporaneity.